THE PARTICIPATION OF PARENTS IN THE DEVELOPMENT OF PUPILS’ READING SKILLS AND INTERESTS - Usca, Svetlana; Rozenfelde, Marite; Ogriņa, Regina; Vindeče, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The skill of reading and comprehension of a written text will have a significant impact on the quality of life: during school years the reading effectiveness ensures optimallearning conditions, but in the long term – inclusion in today's economical, social and cultural processes. The studies on pupils' literacy (OECD, ADORE, etc.) show that the average level of literacy is not high. It is necessary to pay more attention to the pupils' reading skill at the primary school, as well as to the development of reading interests and motivation. Not only teachers but also parents should be actively involved in this process.The aim of the paper – on the basis of literature analysis and obtained questionnaire results of the project „Reading with Ease and Fun – REF”, 2015-1-BG01-KA201-014354, to draw attention to the role of parents and their responsibility in the development of child's reading skill and interest.